Three levels of conclusiveness of legal argumentation - Grzybowski, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
Article presents three analytical perspectives of the problem of closing legal argumentation against the background of the central interpretative assumptions of two leading Polish theories of interpretation, i.e. the clarificative and derivational concept. Author presents thesis that the ability of operative interpretation to regulate social relations is, inter alia, the resultant of conclusiveness of a given interpretative paradigm and the cultural context in which it is embedded. Regardless of the validation of the result of interpretation in the legal discourse, i.e. in the environment of professionals, it is possible that the directives of interpretation, which constitute a cultural artifact, are not fully compatible with the ideological and axiological assumptions of the legal and political culture of a given society, constituting a counter-productive element of that culture.